Hsa_Circ_0098181 Suppresses Hepatocellular Carcinoma by Sponging miR-18a-3p and Targeting PPARA - Luo, Yuan-Yuan; Tao, Ke-Gong; Lu, Yi-Ting; Li, Bin-Bin; Wu, Kai-Ming; Ding, Chen-Hong; Yan, Fang-Zhi; Liu, Yue; Lin, Yong; Zhang, Xin; Zeng, Xin (Frontiers in Pharmacology, 2022)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths, and its incidence is still high in China. This study aimed to investigate the circular RNAs (circRNAs) involved in the development of HCC and elucidate the mechanism. RNA sequencing found 72 downregulated circRNAs and 88 upregulated circRNAs in human HCC tissues, including hsa_circ_0098181, hsa_circ_0072309, hsa_circ_0000831, hsa_circ_0000231, etc. The reduction of hsa_circ_0098181 was confirmed in 8 paired human HCC tissues, hepatoma cell lines and CCL4/DEN induced mice HCC models by RT-qPCR. FISH assay revealed that hsa_circ_0098181 mainly located in the cytoplasm of hepatocytes in the paratumor tissues. Further log-rank analysis performed in 91 HCC patients demonstrated that low expression of hsa_circ_0098181 was related to poor prognosis. The plasmid and lentivirus overexpressing hsa_circ_0098181 were delivered into HCC cell lines. After hsa_circ_0098181 was upregulated, the proliferation, invasion, migration, colony formation of HCC cell lines were inhibited and the apoptosis were promoted. Moreover, exogenous hsa_circ_0098181 delivery mitigated the tumor formation ability of Huh7 in Balb/C nude mice. Dual-luciferase reporter assay and RIP assay verified that hsa_circ_0098181 sponged miR-18a-3p to regulate PPARA. In addition, rescue experiment found miR-18a-3p mimic partly reversed the suppression of hsa_circ_0098181 on proliferation, invasion and migration of HCC cell lines. In conclusion, hsa_circ_0098181 can repress the development of HCC through sponging miR-18a-3p and promoting the expression of PPARA in vitro and in vivo, and hsa_circ_0098181 might be a therapeutic target for HCC.